2016
DOI: 10.1016/j.oraloncology.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the oral cancer lncRNAome: Identification of novel lncRNAs associated with malignant progression and HPV infection

Abstract: Objectives The role of long non-coding RNA (lncRNA) expression in human head and neck squamous cell carcinoma (HNSCC) is still poorly understood. In this study, we aimed at establishing the onco-lncRNAome profiling of HNSCC and to identify lncRNAs correlating with prognosis and patient survival. Materials and Methods The Atlas of Noncoding RNAs in Cancer (TANRIC) database was employed to retrieve the lncRNA expression information generated from The Cancer Genome Atlas (TCGA) HNSCC RNA-sequencing data. RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 58 publications
6
60
0
Order By: Relevance
“…edu/). Paired LINC00271 expression data in tumor and normal tissues were retrieved from TCGA RNA-sequencing data of PTC, BRCA, LUAD, KIRP, HNSCC, LIHC and PRAD by employing The Atlas of Noncoding RNAs in Cancer (TANRIC)33 (http://ibl.mdanderson.org/tanric/design/basic/index.html) and Gene Expression Omnibus data with accession number GSE3557036 (https://www.ncbi.nlm.nih.gov/geo/). …”
Section: Methodsmentioning
confidence: 99%
“…edu/). Paired LINC00271 expression data in tumor and normal tissues were retrieved from TCGA RNA-sequencing data of PTC, BRCA, LUAD, KIRP, HNSCC, LIHC and PRAD by employing The Atlas of Noncoding RNAs in Cancer (TANRIC)33 (http://ibl.mdanderson.org/tanric/design/basic/index.html) and Gene Expression Omnibus data with accession number GSE3557036 (https://www.ncbi.nlm.nih.gov/geo/). …”
Section: Methodsmentioning
confidence: 99%
“…There is increasing evidence that aberrant expression of lncRNA plays a role in the genesis and progression of HNSCC . Through our present study, we were able to identify and validate 5 differentially expressed lncRNA in HPV‐negative HNSCC ( SPRY4‐IT1 , HEIH , LUCAT1 , LINC00152 , and HAND2‐AS1 ).…”
Section: Discussionmentioning
confidence: 68%
“…There is increasing evidence that aberrant expression of lncRNA plays a role in the genesis and progression of HNSCC. 24,25 Through our present study, we were able to identify and validate 5 differentially expressed lncRNA in HPV-negative HNSCC (SPRY4-IT1, HEIH, LUCAT1, LINC00152, and HAND2-AS1). Further, we found that low expression of MEG3 was associated with more favorable 3- year RFS, although the significance of this finding is unclear.…”
Section: Discussionmentioning
confidence: 76%
“…5b). Interestingly, 4 lncRNA genes from c1 and 10 from c2 have been shown to be overexpressed in the larynx (Additional file 1: Table S6) [20]. Finally, we found that c1 patients are younger than the remaining patients (58.2 versus 61.6 years, p val = 0.018 after T test), and c2 patients older (65 versus 60.2 years, p val = 0.001 after T test) (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, 16 out of 245 lncRNAs in cluster c5, depleted in TP53 mutations (Fig. 2c, d), have been shown to be overexpressed in TP53 wild type HNSCC samples [20]. In addition, 12 out of 245 c5 lncRNA genes were found upregulated in HPV-infected samples [20], in line with high frequency of HPV-positive samples in this cluster (Fig.…”
Section: Resultsmentioning
confidence: 75%